Remaining Service Life Struktur Conveyor E pada Tambang Batubara PT XYZ di Kabupaten Tanah Laut, Provinsi Kalimantan Selatan - Lesmana Eka Fadhilah; Elfida Moralista; Zaenal (Bandung Conference Series: Mining Engineering, 2022)
Abstract. Conveyor is a tool made of carbon steel base material to move coal efficiently. Characteristics of carbon steel in addition to having a strong structure also has properties that are prone to oxidation. This can result in corrosion of the conveyor structure so that it can reduce the value of the Remaining Service Life of the conveyor structure. The research was conducted to determine the type of corrosion, the rate of corrosion, the value of the Remaining Service Life and the control of corrosion on the conveyor structure. Therefore, it is necessary to carry out a corrosion control process so that it can increase the value of the Remaining Service Life of the conveyor structure.The research method used is measuring the thickness reduction of the conveyor structure using the Smart sensor Ultrasonic Thickness Gauge TT 130. The study was conducted on a conveyor structure with dimensions of 90 meters which is divided into 3 segments with 25 test points. The type of corrosion that occurs in the conveyor structure in the study area is uniform corrosion. The corrosion control method used is the coating method with a 3 layer system using a Seaguard 5000 primer coating, Sherglass FF intermediate coating and Aliphatic Acrylic Modified Polyurethane top coating. The value of the Corrosion Rate on the conveyor structure is 0.1683 – 0.3917 mm/year which is included in the good category when viewed based on the table of the relative corrosion resistance of steel. Conveyor structure with a service life of 6 years based on the calculation, the value of Remaining Service Life is 5.05-14.16 years. Therefore, there are 13 test points or 52% which are predicted not to reach the predetermined design life of 15 years. Abstrak. Conveyor merupakan suatu alat angkut yang terbuat dari bahan dasar baja karbon untuk memindahkan bahan galian batubara secara efisien. Karakteristik dari baja karbon selain memiliki struktur yang kuat juga memiliki sifat yang rawan terhadap oksidasi. Hal ini dapat mengakibatkan terjadinya korosi pada struktur conveyor sehingga dapat mengurangi nilai Remaining Service Life struktur conveyor. Penelitian dilakukan untuk mengetahui jenis korosi, nilai Corrosion Rate, nilai Remaining Service Life dan pengendalian korosi pada struktur conveyor. Oleh karena itu perlu dilakukan proses pengendalian korosi sehingga dapat meningkatkan nilai Remaining Service Life struktur conveyor. Metode penelitian yang digunakan yaitu pengukuran pengurangan ketebalan struktur conveyor yang dilakukan dengan menggunakan alat Smart sensor Ultrasonic Thickness Gauge TT 130. Penelitian dilakukan pada struktur conveyor dengan dimensi 90 meter yang terbagi menjadi 3 segmen 25 test point. Jenis korosi yang terjadi pada struktur conveyor yaitu korosi merata. Metode pengendalian korosi yang dipakai yaitu metode coating dengan sistem 3 layer menggunakan primer coating Seaguard 5000, intermediate coating Sherglass FF dan top coating Aliphatic Acrylic Modified Polyurethane. Nilai Corrosion Rate pada struktur conveyor yaitu 0,1683 – 0,3917 mm/tahun dan berdasarkan tabel ketahanan korosi relatif baja termasuk ke dalam kategori good. Struktur conveyor dengan umur pakai 6 tahun berdasarkan perhitungan diperoleh nilai Remaining Service Life yaitu 5,05-14,16 tahun. Oleh karena itu terdapat 13 test point atau 52% yang diprediksi tidak dapat mencapai umur desain yang telah ditentukan yaitu 15 tahun.